INVESTIGATION OF TRANSITION METAL OXIDE ELECTRON TRANSPORTING LAYER FOR INVERTED PM6:Y6 POLYMER SOLAR CELLS - Zinedenova, Aruzhan (Nazarbayev University School of Engineering and Digital Sciences, 2024)
The field of renewable energy has notably boosted over time, whereas the demand for more efficient and sustainable solar cell technologies is taking central attention. Among the various photovoltaic structures, organic photovoltaic (OPV) devices have emerged as promising candidates due to their cost-effectiveness, adaptability, and ease of management. However, the journey towards realizing the full potential of OPVs has been hindered by two critical challenges: rapid degradation and low efficiency. The issue of stability can be addressed by implementing an other structural configuration, namely inverted OPV devices. In comparison to regular devices, inverted OPVs exhibit longer lifetimes, addressing the stability concern. Nevertheless, they suffer from low device efficiency. The primary goal of this research is to identify the proper materials among different metal oxides and to optimize them through multilayering, interlayering, and additive engineering for an efficient ETL structure for future flexible, integrated, and semitransparent electrode devices.
Keywords: solar cell; metal oxides; electron transport layer; organic materials; Type of access: Embargo